IMPLEMENTASI ECO-ENZYM SEBAGAI PRODUK OLAHAN SAMPAH ORGANIK UNTUK PUPUK KOMPOS CAIR DI DESA MANGGA DUA - Lubis, Lailatul Husna; Faruqi, Muhammad; Wulandari, Siti Zahara; Hanova, Yudha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service activity took place in Mangga Dua Village. The goal was to increase residents' understanding of and skills in using eco-enzymes, which are processed organic waste products. The program included socialization and explanations on how to make eco-enzymes from household waste. Participants then implemented the eco-enzymes on water spinach plants as a multifunctional liquid fertilizer. Community participation was high, and residents' understanding of eco-enzymes increased significantly, from 25% before the activity to 85% after. In addition to using eco-enzymes as an organic liquid fertilizer, the community learned about their benefits as natural cleaning agents and environmentally friendly disinfectants. Through this activity, the community gained alternative solutions for organic waste management that support sustainable agricultural practices, raise environmental awareness, and open up economic opportunities for the village.